Analisis Kinerja 14 Reksa Dana Saham Terbaik Periode 2010 - sun, Yen (Bina Nusantara University, 2011)
Capital Market is a significant indicator of an economy for a country. However, in Indonesia many people are not familiar yet with the investment activity in capital market. The writer is then interested to study the performance of the best (15) mutual fund (shares) 2010 version of Investor Magazine for the next period investment decision in 2011. The research will be focused on several stages. First, it will compute the return for 14 mutual funds, market return and risk-free rate for one year period. Then, the performance will be evaluated using Sharpe, Treynor to find which mutual fund outperform the market. Also, each method will result rank of the best mutual fund. Furthermore, there is one more method will be used in performance evaluation, Jensen. The result of this study is there are two mutual funds that can be recommended for investment in 2011, they are Panin Dana Maksima and Panin Dana Prima. They are recommended because the two mutual funds showed the best performance for those three methods of evaluation and they can maintain their performance for more than one period.Â